2020
DOI: 10.3390/antibiotics9090528
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Murine Skin Model for B. burgdorferi Biofilm

Abstract: Borrelia burgdorferi, the causative agent of Lyme disease, has been recently shown to form biofilm structures in vitro and in vivo. Biofilms are tightly clustered microbes characterized as resistant aggregations that allow bacteria to withstand harsh environmental conditions, including the administration of antibiotics. Novel antibiotic combinations have recently been identified for B. burgdorferi in vitro, however, due to prohibiting costs, those agents have not been tested in an environment that can mimic th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 85 publications
(135 reference statements)
0
5
0
Order By: Relevance
“…Finally, tissues were embedded horizontally in molten paraffin. Embedded zebrafish blocks (both infected and uninfected) were sectioned at 4 μm, deparaffinized, then stained with a Borrelia polyclonal antibody diluted to 1:50 in 1x PBS (ThermoFisher, Waltham, MA, USA; FITC-PA1-73005) according to a previously established protocol [31]. Negative control slides omitted the primary Borrelia antibody.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, tissues were embedded horizontally in molten paraffin. Embedded zebrafish blocks (both infected and uninfected) were sectioned at 4 μm, deparaffinized, then stained with a Borrelia polyclonal antibody diluted to 1:50 in 1x PBS (ThermoFisher, Waltham, MA, USA; FITC-PA1-73005) according to a previously established protocol [31]. Negative control slides omitted the primary Borrelia antibody.…”
Section: Methodsmentioning
confidence: 99%
“…While there is some utility to pursue the development of non-mammalian models of biofilm-infection such as Drosophila melanogaster , Galleria mellonella or Danio rerio (Zebrafish) ( Lebeaux et al., 2013 ), identification of ex vivo models that recreate the infectious environment should be encouraged. Among recently developed ex vivo models are, for example, an ex vivo pig lung biofilm model used for understanding antibiotic tolerance of P. aeruginosa biofilms ( Hassan et al., 2020 ) or an ex vivo murine skin biopsy model to characterize B. burgdoferi biofilms, the etiological agent of Lyme disease ( Torres et al., 2020 ). Last but not least with the development of reconstituted organs such as organoids or organ-on-a-chip, one could anticipate that adaptations of these models to the understanding of the physiopathology of biofilm infections, interactions of biofilms with the immune response or biofilm behaviors in the presence of antimicrobials would provide important information relevant to biofilms in infectious contexts ( Jimi et al., 2017 ; Choi et al., 2020 ; Yuan et al., 2020 ).…”
Section: Challenges In Methods For Investigating Biofilmsmentioning
confidence: 99%
“…These results suggest that round bodies might play a certain role in LD pathogenesis [ 268 ]. Using an ex-vivo murine skin model, it was observed that Borrelia can also form biofilm-like colonies made by spiral-shaped bacteria [ 274 ]. Biofilm represents an alternative lifestyle in which the microbes grow as structrured aggregates and adopt a multicellular behaviour that facilitates their survival under unfavourable conditions.…”
Section: Alternative Pathogenic Mechanismsmentioning
confidence: 99%